US Medicaid program: An analysis of the spending and utilization patterns for antidepressants from 2017 to 2021 - Mohamed Elmarasi; Brian Fuehrlein (Elsevier, 2024)
Background: Major depressive disorder (MDD) is a serious mental health condition that contributes to health complications, financial burden and death. In 2020, about one in five US adults had a lifetime diagnosis of MDD. With Major Depressive Disorder (MDD) being a common mental health concern, it is important to understand treatment patterns within public health systems like Medicaid, as they play a crucial role in providing care to diverse populations. Objective: The study investigated antidepressant usage and market distribution in the Medicaid Program. By doing so, the study aimed to provide insights into how these trends reflect broader changes in mental health treatment practices and policy implications within the Medicaid system during the study period. Methods: Public Medicaid data from 2017 to 2021 were analyzed, focusing on 30 FDA-approved antidepressants. Spending and prescription data were aggregated using Excel and Python. Results: The total US Medicaid expenditure on antidepressants increased from about $1 billion dollars in 2017 to $1.12 billion dollars in 2021, an increase of about 10%. Consistently, SSRIs were the class of antidepressants that Medicaid spent the most on. The highest Medicaid spending on a single antidepressant in 2017 and 2018 was bupropion. During the remaining years of the study (2019, 2020, 2021) Medicaid appropriated most funds toward Vortioxetine. The total number of antidepressant prescriptions increased from 52 million scripts to 59 million scripts (an increase of about 14%). Conclusions: The increase in Medicaid spending on antidepressants during the study period can be explained by an increase in utilization (a 14% increase in antidepressant prescriptions from 2017 to 2021), and a shift toward prescribing newer more costly antidepressants (like SSRIs and others) and away from prescribing older, less costly antidepressants like monoamine oxidase inhibitors (MAOIs) and tricyclic antidepressants (TCAs)."